La mer et Saint-Malo à la fin du Moyen-Age. L’appareillage de la pérennité - Emmanuel Chevet (Carnets)
Saint-Malo is baptized the “Nid des Corsaires”. It is the most glistening port in the Louis XIV’s kingdom (Lespagnol, 1995). How not to hold the famous names to which gives birth Saint-Malo, with a sailor such as Jacques Cartier or privateers as René Duguay-Trouin and Robert Surcouf? Saint Malo's prosperity in the Modern period and offspring of its famous names, can be understand only in ferments’ prospect carried out by other malouins, which footnotes of history was repulsed in the shade of greatest one. Include Saint Malo in the XIVth century requires a dichotomous reading. On one hand, the city joins in the continuity towards its past, that of three men’s types independance, in the triple legacy’s bloodline, the crossroads of an unchanging sea; on the other hand, it evolves with regard to his its time, there also according to the sea, politically as economically.